Taṣmīm Māddah al-Muḥādaṡah Bi Mauḍū al-Bīah al-Ma`hadiyah (Dirāsah al-Baḥṡ Wa at-Taṭwīr `An al-Qāmūs al-Ma`hadī Bi Ma`had Dār al-Iḥsān Abu Hasan Krueng Kalee-Aceh Besar) - Magdalena Magdalena; Zulhelmi Zulhelmi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
This title is chosen by the writer because of the absence of particular books for Arabic conversation of the student as well as interviewed the head of language center of the school, Dr. Muakhir Zakaria MA. Theses questioner yield that the student need certain guidance books used to improve their capability in Arabic conversation. The purpose of this study is to figure out the application of this material design and to measure the effectivenees of the design of under the title “The environment of Islamic boarding school” to improvew student’s ability. The writer used RND method and takes the entire student of this boarding school as the population, while the sample is student from class 2D which are 30 student. Morevere, in data collection, the writer does observation, interviews, questioner and test. Pre-test result of this test is 62% and post-test 75% and it is more effective for them to us.